CLASSICAL, NON-CLASSICAL, AND POST-NON-CLASSICAL RATIONALITY: STRUCTURAL CORRELATION AND EPISTEMIC VULNERABILITY IN THE CONTEXT OF CYBER SOCIETY - Khrystokin, Hennadiі; Verkhovtseva, Iryna; Slyusar , Vadym (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Rationality is no longer a purely academic issue. In the context of large-scale information conflicts, the digital transformation of the public sphere, and Russia’s armed aggression against Ukraine, dominant conceptions of rationality in public discourse shape a society’s ability to distinguish knowledge from propaganda, argument from manipulation, and expertise from rhetorical legitimation. S. Vosoughi, D. Roy, and S. Aral have shown that false information spreads faster and more widely than truth, largely because of human behaviour within algorithmically structured environments. Russia’s full-scale war against Ukraine is therefore not only a military confrontation but also an informational and epistemic conflict aimed at cognitive disorientation and the erosion of truth-establishing procedures. The aim and tasks. The article aims to substantiate the concept of structural correlation of classical, non-classical and post-non-classical rationality as both an analytical concept and a practical criterion of cognitive security of the state in the conditions of a digital cyber-society and informational aggression. Research methods. The study draws on Stepin’s typology of scientific rationality, Longino’s social epistemology, Habermas’s theory of communicative and strategic action, and the approaches of Latour and Floridi to analyse the digital environment. The concept of structural correlation is grounded in Husserl’s notion of correlation as necessary interdependence without fusion. Research results. Classical rationality secures fact verification and an ontological reference point; non-classical rationality enables critique of positionality and source transparency; post-non-classical rationality analyses the systemic effects of digital platforms on public cognition. The article defines their structural correlation as a necessary interdependence and argues that non-classical and post-non-classical rationality are especially vulnerable to manipulation, since their reflexive concepts can be turned into rhetorical devices for relativising facts and diffusing responsibility. The case of Russian propaganda shows how such de-instrumentalisation of rationality undermines trust in verified knowledge. Discussion. The discussion argues that the concept of the structural correlation of rationalities bridges the philosophy of rationality and disinformation studies by showing that epistemic chaos is effective because it disrupts the functional interdependence of classical, non-classical, and post-non-classical rationality, an interdependence that Longino’s account of objectivity helps illuminate as a condition of cognitive security. Conclusions. Cognitive security of the state is defined as the preservation of conditions under which all three types of rationality function simultaneously in the public space. Three operational criteria are proposed: whether independent fact verification retains social authority; whether algorithmic systems are transparent; and whether systemic conditions enabling manipulation are analysed. The destruction of any pole of the structural correlation constitutes a strategic objective of epistemic aggression and its protection is therefore not an academic but a directly social and security matter